THE INTRODUCTION OF NEW RAIL TRACK STRUCTURES ON THE RAILWAYS OF UKRAINE - Demchenko, S. M. (Science and Transport Progress, 2003)
The passed stages and prospects of the track construction development are analyzed in condition of the shaping the transport system of transportation of theUkraine.